When is a wolf a dog? Combined geometric morphometrics and stable isotope analyses for differentiating wild from domestic canids on the Northern Plains. (2nd October 2019) - Fisher, Abigail E.
Abstract : Domesticated dogs ( Canis familiaris ) were an important resource for many indigenous groups, including Plains peoples. Plains people used dogs for hauling materials, as camp or village warning systems, as sources of food, and as ritual participants. The identification of domestic Plains dogs is complicated by their wolf-like body size, and from hybridization with Canis lupus and Canis latrans, which also appear in the archaeological record. By combining stable carbon, nitrogen, and oxygen isotope analyses with geometric morphometric studies of canid mandibles and lower teeth from Plains Village sites in North Dakota, this article presents a methodology for differentiating wild and domestic canids. GRAPHICAL ABSTRACT: